Functional current collector and preparation method and application thereof

By coating a two-dimensional hybrid organic-inorganic perovskite coating on the surface of the polymer base film, the residual stress problem caused by high temperature during the coating process of the functional current collector is solved, and the effect of improving its mechanical strength and thermal stability is achieved.

CN119764456AActive Publication Date: 2025-04-04JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510272566.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

During the coating process, the existing functional current collectors have plastic deformation and thermal stress caused by high temperature, resulting in large residual stress, affecting its thermal stability and mechanical strength.

Method used

A hybrid organic-inorganic perovskite coating is coated on the surface of the polymer base film. This coating consists of two-dimensional hybrid organic-inorganic perovskite material, with high hardness, high tensile strength and good thermal insulation, reducing thermal and tensile stress.

Benefits of technology

It effectively reduces the residual stress of the functional current collector, improves its mechanical strength and thermal stability, and optimizes the battery cycle performance and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The invention provides a functional current collector and a preparation method and application thereof. The functional current collector sequentially comprises a base film, a hybrid organic-inorganic perovskite coating and a metal layer, the material of the hybrid organic-inorganic perovskite coating comprises a two-dimensional hybrid organic-inorganic perovskite material; the two-dimensional hybrid organic-inorganic perovskite material comprises at least one of an achiral two-dimensional hybrid organic-inorganic perovskite material, a mixed achiral two-dimensional hybrid organic-inorganic perovskite material, a semi-chiral two-dimensional hybrid organic-inorganic perovskite material and a full-chiral two-dimensional hybrid organic-inorganic perovskite material. The functional current collector has relatively low residual stress, and the thermal stability and mechanical strength of the functional current collector are effectively enhanced, so that the stability of the battery in the charge-discharge cycle process is optimized, and the cycle performance and thermal stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery current collectors, and in particular relates to a functional current collector and a preparation method and application thereof. Background Art

[0002] Residual stress is an important issue in thin film applications because it can limit the performance range or cause failure stress. The stress generated by the processes occurring during the deposition of thin films is usually called intrinsic stress. But stress can also be generated by effects that occur after deposition, such as thermal expansion mismatch between the film and the substrate or grain growth in films with sufficient atomic mobility. Different deposition methods, where the deposited material has low energy (such as evaporation, electrodeposition) or high energy (such as sputtering deposition), can also lead to very different stress states. In general, the adhesion of the coating on the substrate depends on some characteristics of the interface area, including the type of bonding between the coating and the substrate, the microstructure and the stress state. The total stress in the coating consists of thermal stress and intrinsic stress. Thermal stress is caused by the inconsistency between the thermal expansion coefficient of the coating and the thermal expansion coefficient of the substrate. Intrinsic stress is generated during the growth of the coating, caused by factors such as impurity incorporation and structural reordering. At the same time, the presence of surface tension during the winding and unwinding process can also lead to changes in film surface stress, thereby affecting the internal stress between the molecules in the coating.

[0003] During the coating process (vacuum coating / magnetron), the temperature in the sputtering chamber / evaporation chamber is high, and the commonly used polymer base film such as PET base film will undergo plastic deformation at high temperature, resulting in tensile stress in the subsequent process. In addition, thermal stress will be generated during the heat transfer process when the high-temperature evaporating gas contacts the low-temperature base film. At the same time, when the gas is deposited on the base film, some of the collisions reduce the kinetic energy carried, while some of the collisions carry higher kinetic energy. During the contact between these molecules and the film, the kinetic energy released causes uneven internal stress between the coating and the base film.

[0004] In the preparation of the functional current collector, a coating is usually deposited on a polymer base film. Therefore, the functional current collector also has the tensile stress, thermal stress, and internal stress problems mentioned above, which makes the residual stress of the formed functional current collector large, affecting the thermal stability and mechanical strength of the functional current collector. Summary of the invention

[0005] In order to solve the problems and deficiencies in the prior art, the present invention provides a functional current collector and its preparation method and application. The functional current collector is first coated with a layer of hybrid organic-inorganic perovskite coating on the surface of the polymer base film. The material of the coating adopts a two-dimensional hybrid organic-inorganic perovskite material. Therefore, the coating formed has high hardness, high tensile strength and good thermal insulation effect, which can effectively block the influence of heat generated by the evaporation / magnetron deposition coating process on the thermal stress of the base film surface, and reduce the deformation caused by the tension during the winding process of the film surface, and reduce the strain force. Therefore, the functional current collector finally prepared has a lower residual stress, effectively enhances the thermal stability and mechanical strength of the functional current collector, and then optimizes the stability of the battery during the charge and discharge cycle, and improves the battery cycle performance and thermal stability.

[0006] According to the first aspect of the present invention, a functional current collector is provided, which comprises a base film, a hybrid organic-inorganic perovskite coating, and a metal layer in sequence; the material of the hybrid organic-inorganic perovskite coating comprises a two-dimensional hybrid organic-inorganic perovskite material; the two-dimensional hybrid organic-inorganic perovskite material comprises at least one of an achiral two-dimensional hybrid organic-inorganic perovskite material, a mixed achiral two-dimensional hybrid organic-inorganic perovskite material, a semi-chiral two-dimensional hybrid organic-inorganic perovskite material, and a fully chiral two-dimensional hybrid organic-inorganic perovskite material.

[0007] At present, the application of hybrid organic-inorganic perovskite materials is mainly in the field of solar cells, mainly using their excellent optoelectronic properties. These properties include adjustable optical band gap, high light absorption coefficient, low exciton dissociation energy, etc. These properties make perovskite materials widely used in the photovoltaic field. Therefore, hybrid organic-inorganic perovskite materials are rarely used in the field of lithium batteries, especially in the field of lithium battery current collectors.

[0008] At present, hybrid organic-inorganic perovskite materials are mainly composed of two-dimensional hybrid organic-inorganic perovskite materials and three-dimensional hybrid organic-inorganic perovskite materials. The main difference between two-dimensional hybrid organic-inorganic perovskite and three-dimensional hybrid organic-inorganic perovskite is their structural dimension and composition. Two-dimensional hybrid organic-inorganic perovskite adopts a layered structure in which organic cation layers and inorganic anion skeletons are loosely connected and alternate with each other. This structure provides a rich material platform, and through strategies such as molecular modification and molecular self-assembly, the design and regulation of relevant functional properties can be achieved. Three-dimensional hybrid organic-inorganic perovskite is composed of organic and inorganic components alternately combined in three-dimensional space, forming a continuous crystal structure. Moreover, because the organic and inorganic parts in the structure of three-dimensional hybrid organic-inorganic perovskite materials are connected by weak interactions, such as hydrogen bonds or van der Waals forces, their structural stability is poor when facing external environmental factors such as humidity and temperature changes, and they are prone to degradation or phase change. In contrast, two-dimensional hybrid organic-inorganic perovskite materials have higher structural stability, thanks to their special layered structure, in which the organic cation layers and the inorganic anion skeleton are loosely connected and alternate with each other, forming a relatively stable structure.

[0009] Therefore, the present invention selects a two-dimensional hybrid organic-inorganic perovskite material with better stability to form a hybrid organic-inorganic perovskite coating on a polymer base film, especially the non-chiral, mixed non-chiral, semi-chiral, and fully chiral two-dimensional hybrid organic-inorganic perovskite materials listed above, whose structures produce π-π and CH-π interactions on the organic-organic interface, which can effectively increase the interaction between structures while reducing the thermal conductivity. Therefore, firstly, the hybrid organic-inorganic perovskite coating formed by it can have high hardness and high tensile strength, and then the base film containing the hybrid organic-inorganic perovskite coating and the functional current collector finally obtained also have high hardness and high tensile strength, thereby effectively reducing the deformation caused by the tension in the film surface winding process in each step of preparing the functional current collector, and reducing the tensile residual stress. Secondly, the hybrid organic-inorganic perovskite coating formed by the method can have a low thermal conductivity and high density, which can play a good role in heat insulation for the polymer base film, so that in the process of continuing to deposit the oxide coating and metal layer by evaporation / magnetron, the influence of high temperature on the polymer base film can be reduced, and the stress caused by thermal deformation can be effectively reduced. Thirdly, because the surface of the polymer base film is coated with this layer of high hardness and high tensile strength hybrid organic-inorganic perovskite coating, the high energy bombardment caused by the process of continuing to deposit the oxide coating and metal layer by evaporation / magnetron can reduce the perforation of the polymer base film surface caused by the high energy bombardment caused by the process of continuing to deposit the oxide coating and metal layer by evaporation / magnetron, so as to further improve the structural strength of the functional current collector, optimize the stability of the functional current collector in the battery cycle, and then optimize the battery cycle performance and thermal stability.

[0010] It should be noted here that the difference between achiral, mixed achiral, semi-chiral and fully chiral two-dimensional hybrid organic-inorganic perovskite materials is that achiral refers to molecules that do not have chiral carbon and chiral centers; mixed achiral refers to molecules formed by the combination of two achiral molecules; semi-chiral refers to molecules formed by the combination of chiral and achiral molecules; fully chiral refers to molecules with exactly the same molecular structure but opposite left-right arrangements, such as the real object and its mirror image.

[0011] Preferably, the thickness of the hybrid organic-inorganic perovskite coating is 130-170 nm. Controlling the thickness of the hybrid organic-inorganic perovskite coating within the above range can not only effectively insulate and improve hardness and tensile strength, effectively relieve thermal stress and tensile stress, reduce thermal deformation and tensile deformation, and reduce overall residual stress, but also effectively avoid the perforation of the polymer base film surface caused by high-energy bombardment caused by the deposition of other coating processes, and effectively optimize the mechanical strength and thermal stability of the functional current collector; it can also take into account that the overall functional current collector has a more appropriate thickness, avoiding the functional current collector from being too thick to affect the energy density of the battery, and avoiding the hybrid organic-inorganic perovskite coating from being too thick to affect the conductivity or other properties of the functional current collector itself.

[0012] Preferably, when the material of the hybrid organic-inorganic perovskite coating includes an achiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 145~155nm; when the material of the hybrid organic-inorganic perovskite coating includes a mixed achiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 155~165nm; when the material of the hybrid organic-inorganic perovskite coating includes a semi-chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 135~145nm; when the material of the hybrid organic-inorganic perovskite coating includes a chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 148~158nm. When the materials of the hybrid organic-inorganic perovskite coating are achiral, mixed achiral, semi-chiral, and fully chiral two-dimensional hybrid organic-inorganic perovskite materials, respectively, controlling the thickness of the formed hybrid organic-inorganic perovskite coating to be within the above-mentioned range is more conducive to alleviating the thermal stress and tensile stress in the process of preparing the functional current collector, while effectively insulating and making the comprehensive stability of the functional current collector higher, and can further take into account the battery's cycle performance, safety performance, energy density and other aspects of performance.

[0013] Preferably, the achiral two-dimensional hybrid organic-inorganic perovskite material includes [C4A]2PbI4; the mixed achiral two-dimensional hybrid organic-inorganic perovskite material includes [C4A]2[PEA]PbI4; the semi-chiral two-dimensional hybrid organic-inorganic perovskite material includes [SMePEA]2[C3A]PbI4; the chiral two-dimensional hybrid organic-inorganic perovskite material includes [SMePEA]2PbI4; wherein, in [C4A]2PbI4, [C4A]2[PEA]PbI4, [SMePEA][C3A]PbI4 and [SMePEA]2PbI4, C4A is C4NH3 + , PEA is , S indicates that the structure is left-handed, Me is methyl, SMePEA is , C3A is In practical applications, the above-mentioned specific two-dimensional hybrid organic-inorganic perovskite materials can effectively reduce thermal stress and tensile stress, that is, effectively reduce the residual stress in the preparation process of the functional current collector, optimize the mechanical strength and thermal stability of the functional current collector, and optimize the battery performance.

[0014] Preferably, when the material of the hybrid organic-inorganic perovskite coating includes at least one of a non-chiral two-dimensional hybrid organic-inorganic perovskite material and a mixed non-chiral two-dimensional hybrid organic-inorganic perovskite material. Compared with semi-chiral and chiral two-dimensional hybrid organic-inorganic perovskite materials, non-chiral and mixed non-chiral two-dimensional hybrid organic-inorganic perovskite materials usually have a lower alkyl carbon chain length, and thus a lower thermal conductivity and a higher hardness, just as non-chiral, mixed non-chiral, semi-chiral, and fully chiral two-dimensional hybrid organic-inorganic perovskite materials, in the process of changing from non-chiral to chiral two-dimensional hybrid organic-inorganic perovskite materials, the thermal conductivity will increase and the hardness will decrease. Therefore, the hybrid organic-inorganic perovskite coating formed by non-chiral and mixed non-chiral two-dimensional hybrid organic-inorganic perovskite materials has better thermal insulation performance, higher hardness and tensile strength, and can more significantly reduce the thermal stress and tensile stress in the preparation process of the functional current collector, that is, more significantly reduce the residual stress, and is more conducive to the improvement of the mechanical strength and thermal stability of the functional current collector.

[0015] It should also be noted here that in these two-dimensional hybrid organic-inorganic perovskite materials, as the length of the alkyl carbon chain of the organic part increases, the thermal conductivity and hardness will decrease. Therefore, it is also necessary to properly control the length of the alkyl carbon chain of the organic part so that the coating formed by the two-dimensional hybrid organic-inorganic perovskite material has better thermal insulation, hardness and tensile properties.

[0016] Preferably, the thickness of the base film is 6-8 μm; the thickness of the metal layer is 0.8-1.2 μm. Controlling the thickness of the base film and the metal layer within the above range can make the functional current collector have better mechanical properties and conductive properties, while not causing the battery energy density to decrease due to the functional current collector being too thick.

[0017] Preferably, the functional current collector comprises a base film, a hybrid organic-inorganic perovskite coating, an oxide coating, and a metal layer in sequence. An oxide coating is provided between the hybrid organic-inorganic perovskite coating and the metal layer. In the functional current collector, the ceramic layer is deposited before the metal layer is deposited. The oxide layer is mainly used to improve the mechanical properties of the functional current collector, meet the preparation process requirements of the battery pole sheet coating and rolling process, and thus improve the overall performance and reliability of the battery.

[0018] Preferably, the thickness of the oxide coating is 0.5-20 nm. Similarly, the thickness of the oxide coating also needs to be within a certain numerical range, so that the mechanical properties and conductivity of the functional current collector and the energy density of the battery can be taken into account.

[0019] Preferably, the material of the base film includes at least one of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide; Preferably, the material of the oxide coating layer includes at least one of aluminum oxide and silicon oxide. Preferably, the material of the oxide coating layer includes aluminum oxide.

[0020] Preferably, the material in the metal layer includes at least one of aluminum and copper. Preferably, the material in the metal layer includes aluminum.

[0021] According to the second aspect of the present invention, a method for preparing the above-mentioned functional current collector is provided, comprising the following steps: S1. preparing a hybrid organic-inorganic perovskite mixed solution, applying the mixed solution to the surface of the base film, and drying to form a hybrid organic-inorganic perovskite coating on the surface of the base film; S2. continuing to deposit an oxide coating on the surface of the hybrid organic-inorganic perovskite coating; the deposition method includes at least one of magnetron sputtering and vacuum coating; S3. continuing to deposit a metal layer on the surface of the oxide coating; the deposition method includes at least one of magnetron sputtering and vacuum coating. The functional current collector prepared by the above steps has uniform and dense coating layers, and strong mutual tightness, so that the residual stress in the preparation process of the functional current collector is reduced, and its mechanical strength and thermal stability are optimized.

[0022] Preferably, in S1, during the preparation of the hybrid organic-inorganic perovskite mixed solution, the mass ratio of the hybrid organic-inorganic perovskite powder to the solvent is 2-4:1; the solvent includes water and acetone, and the volume ratio of water to acetone is 1-2:1.

[0023] In summary, the present invention introduces a layer of hybrid organic-inorganic perovskite coating on the surface of the polymer base film, which has high hardness, high tensile strength and good thermal insulation effect, which can effectively block the influence of heat generated by the evaporation / magnetron deposition coating process on the thermal stress of the base film surface, and reduce the deformation caused by the tension during the winding process of the film surface, thereby reducing the strain. Therefore, the overall residual stress of the functional current collector is effectively reduced, the mechanical properties and thermal stability of the functional current collector are improved, and the purpose of optimizing the battery cycle performance and thermal stability is achieved. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.

[0025] Example 1 The functional current collector of this embodiment is prepared according to the following steps: S1. The non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2PbI4 (C4A is C4NH3 + ) is placed in a water / acetone mixture (water / acetone volume ratio = 1.5:1), the mass ratio of [C4A]2PbI4 to the water / acetone mixture is 3:1, and ultrasonic treatment is performed for 30 minutes to make the solid and liquid mixed evenly; the obtained mixed solution is evenly coated on the surfaces of both sides of the PET (polyethylene terephthalate) base film, and dried at 80°C for 20 minutes to form hybrid organic-inorganic perovskite coatings on the surfaces of both sides of the base film; wherein the thickness of the PET base film is 7μm, and the thickness of the hybrid organic-inorganic perovskite coating is 150nm; S2. Then, an alumina coating and an aluminum layer are sequentially deposited on the surfaces of the two hybrid organic-inorganic perovskite coatings. The specific operation is as follows: the film product obtained in S1 is fixed to the winding trolley, and the film is retracted and threaded, and then the tension is adjusted, wherein the film-releasing end is 120N and the rewinding end is 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, start the winding trolley, control the speed at 280~300m / min, heat the evaporation boat and feed the aluminum wire at a speed of 300~350mm / min, start the oxygen intake, and apply aluminum oxide primer on the surface of the base film. The vacuum degree is controlled at 5*10 -2Pa; then the vacuum is broken and the aluminum layer is plated in the same way, with the heating temperature being 1000-1200°C; in this step, the deposition time during the plating is controlled so that the thickness of the aluminum oxide layer on each side is 5nm and the thickness of the aluminum layer is 1μm.

[0026] Example 2 In the process of preparing the functional current collector in this embodiment, the difference from Example 1 is that the non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2PbI4 is replaced by a mixed non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2[PEA]PbI4 (where C4A is C4NH3 + , PEA is ). The remaining operations are consistent with those in Example 1.

[0027] Example 3 In the process of preparing the functional current collector in this embodiment, the difference from Example 1 is that the non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2PbI4 is replaced by a semi-chiral two-dimensional hybrid organic-inorganic perovskite material [SMePEA]2[C3A]PbI4 (where SMePEA is , C3A is ). The remaining operations are consistent with those in Example 1.

[0028] Example 4 In the process of preparing the functional current collector in this embodiment, the difference from Example 1 is that the non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2PbI4 is replaced by a chiral two-dimensional hybrid organic-inorganic perovskite material [SMePEA]2PbI4 (where SMePEA is ). The remaining operations are consistent with those in Example 1.

[0029] Example 5 In the process of preparing the functional current collector in this embodiment, the difference from that in Embodiment 1 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 140 nm. The rest is the same as in Embodiment 1.

[0030] Example 6 In the process of preparing the functional current collector in this embodiment, the difference from that in Embodiment 2 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 170 nm. The rest is the same as in Embodiment 2.

[0031] Example 7 In the process of preparing the functional current collector in this embodiment, the difference from that in embodiment 3 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 130 nm. The rest is the same as in embodiment 3.

[0032] Example 8 In the process of preparing the functional current collector in this embodiment, the difference from that in Embodiment 4 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 165 nm. The rest is the same as that in Embodiment 4.

[0033] Example 9 In the process of preparing the functional current collector in this embodiment, the difference from that in embodiment 3 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 125 nm. The rest is the same as in embodiment 3.

[0034] Example 10 In the process of preparing the functional current collector in this embodiment, the difference from that in Embodiment 2 is that in S1, the coating thickness of the hybrid organic-inorganic perovskite coating is controlled to be 175 nm. The rest is the same as in Embodiment 2.

[0035] Embodiment 11 In the process of preparing the functional current collector in this embodiment, the difference from that in embodiment 1 is that in S2, the coating thickness of the aluminum oxide coating is controlled to be 25 nm. The rest is the same as in embodiment 1.

[0036] Example 12 In the process of preparing the functional current collector in this embodiment, the difference from that in Embodiment 1 is that in S2, the coating thickness of the metal layer is controlled to be 0.6 μm. The rest is the same as that in Embodiment 1.

[0037] Embodiment 13 In the process of preparing the functional current collector in this embodiment, the difference from Example 1 is that in S2, the oxide coating and the metal layer are controlled to be a silicon oxide coating and a copper layer respectively. The specific operation is: then the oxide coating and the copper layer are deposited on the surfaces of the two hybrid organic-inorganic perovskite coatings respectively. The specific process conditions are as follows: (1) the target arrangement is set to 4 silicon oxide targets plus 16 copper targets (purity of 99.95%), and the magnetron sputtering power density is 50W / cm 2 , vacuum degree is 5*10 - 4Pa, the protective gas is argon gas, and the flow rate is 50mL / min; (2) the voltage of the target is set to 200V, the winding is turned on, the speed is 25m / min, the innermost side is the brittle layer (silicon oxide layer), and the outermost side is the copper layer; the deposition time is controlled so that the thickness of the metal layer is 20nm and the thickness of the brittle layer (silicon oxide) is 5nm; (3) the product obtained in (2) is further subjected to chemical plating, first pre-plating, the current size is 0.5-1A, and then the current of each aqueduct is increased, and thickening plating is performed, the current size is 1.2-3.5A; the main component of the selected plating solution is copper sulfate, and the winding speed is 10m / min; so that the thickness of the silicon oxide layer on each side is 5nm, and the thickness of the copper layer is 1μm. The rest is consistent with Example 1.

[0038] Comparative Example 1 In the process of preparing the functional current collector in this comparative example, the difference from Example 1 is that step S1 is not performed, that is, the hybrid organic-inorganic perovskite coating is not coated on the PET base film, but the aluminum oxide layer and the aluminum layer are directly deposited on the PET base film, and step S1 is omitted and step S2 is performed directly. The rest of the operations are the same as in Example 1.

[0039] Comparative Example 2 In the process of preparing the functional current collector in this embodiment, the difference from Example 1 is that the non-chiral two-dimensional hybrid organic-inorganic perovskite material [C4A]2PbI4 is replaced by a chiral three-dimensional hybrid organic-inorganic perovskite material [SMBA]2PbI4 (SMBA is The remaining operations are consistent with those in Example 1.

[0040] Test Case 1. Experimental Construction Method The functional current collectors prepared in the above-mentioned embodiments and comparative examples were tested for thermal deformation, tensile deformation, tensile properties, surface pinholes, residual stress and other related properties.

[0041] (1) Thermal deformation test The functional current collector was sampled, each sample was 5*10cm in size, and placed at different temperatures for 30 minutes. Then, the length change in the MD (longitudinal) direction was measured with a caliper. The thermal elongation was calculated by comparing the length before the experiment. The formula is: Thermal elongation = (L1 形变后 -L1 形变前 ) / L1 形变前 .

[0042] (2) Tensile deformation test The functional current collector was sampled, each sample was 5*10cm in size, and placed under different tensions (proportionately simulated on-site surface tension, for example, the membrane width was 1650mm during production, the tension was about 130N, and the corresponding tension of a 50mm wide sample was about 4N) for 30min at room temperature. Then, the length change in the MD (longitudinal) direction was measured with a caliper. By comparing the length with that before the experiment, the tension extension rate was calculated. The formula is: tension extension rate = (L2 形变后 -L2 形变前 ) / L2 形变前 .

[0043] (3) Tensile properties test The room temperature tensile strength of the functional current collector is tested by an electronic universal material testing machine. The test conditions are: gauge length 10 mm, tensile speed 100 mm / nin, width 15 mm. Other requirements are measured according to the method specified in GB / T 1040.3-2006.

[0044] (4) Surface pinhole test The number of pinholes on the surface of the functional current collector is tested using a CCD machine. Through backlight imaging, a CCD linear array camera installed on the production line is used for real-time synchronous scanning to capture the light leakage points and calculate the number of holes.

[0045] (5) Residual stress test The residual stress of the functional collector is measured by the μ-360s X-ray residual stress tester of QUANTUM Quantum Scientific Instrument Trading (Beijing) Co., Ltd. The specific operation is as follows: the cut sample is placed in the test chamber, the sample is irradiated with X-rays, and after a single angle incident, a complete Debye ring is obtained using a two-dimensional detector. The change in the crystal plane spacing under stress and the corresponding stress are calculated by comparing the difference between the Debye ring without stress and the deformed Debye ring under stress. After applying stress, the change in the Debye ring before and after a single incident is analyzed, and the residual stress data can be obtained through the residual stress analysis software. .

[0046] 2. Experimental results The results of testing the thermal deformation, tensile deformation, tensile properties, surface pinholes, residual stress and other related properties of the functional current collectors prepared in the above embodiments and comparative examples are shown in Tables 1, 2 and 3.

[0047] Table 1 Thermal deformation data of functional current collectors in embodiments and comparative examples (without additional tension)

[0048] Table 2 Tensile deformation data of functional current collectors in embodiments and comparative examples

[0049] Table 3 Tensile strength and surface pinhole data of functional current collectors in examples and comparative examples

[0050] As can be seen from Tables 1 to 3 above, the functional current collector provided by the present invention is first coated with a layer of hybrid organic-inorganic perovskite coating on the surface of the polymer base film. The coating has high hardness, high tensile strength and good thermal insulation effect, so that the functional current collector finally obtained also has high hardness and high tensile strength, thereby effectively reducing the deformation caused by the tension during the winding process of the film surface in each step of preparing the functional current collector, and reducing the tensile residual stress. At the same time, the number of holes caused by aluminum splashing during the production process is reduced. By testing the residual stress of the film surface before and after the improvement, the results show a high improvement, which greatly reduces the residual stress of the film surface. For details, please refer to Examples 1 to 13.

[0051] In Comparative Example 1, the hybrid organic-inorganic perovskite coating is not coated on the PET base film, but the aluminum oxide layer and the aluminum layer are directly deposited on the PET base film. Therefore, the hardness, tensile strength and thermal insulation effect of the functional current collector cannot be improved, and the residual stress in the preparation process of the functional current collector cannot be effectively alleviated. Ultimately, the functional current collector begins to undergo thermal deformation at 180°C, tensile deformation occurs under a tensile force of 5N, the tensile strength is significantly reduced, the number of surface pinholes is significantly increased, and the residual stress is significantly increased.

[0052] In Comparative Example 2, a three-dimensional hybrid organic-inorganic perovskite material is used. Compared with the two-dimensional hybrid organic-inorganic perovskite material, the three-dimensional hybrid organic-inorganic perovskite material has poor structural stability and is prone to degradation or phase change. As a result, the final functional current collector undergoes thermal deformation at 200°C and tensile deformation at 6N, and the tensile strength of the functional current collector is significantly reduced, and the number of surface pinholes and residual stress are also relatively large.

[0053] Further observation of Example 1 and Example 2 to 4 shows that when replaced with other two-dimensional hybrid organic-inorganic perovskite materials, the performance of the functional current collector is also good. And when using non-chiral two-dimensional hybrid organic-inorganic perovskite materials, mixed non-chiral two-dimensional hybrid organic-inorganic perovskite materials, semi-chiral two-dimensional hybrid organic-inorganic perovskite materials, and chiral two-dimensional hybrid organic-inorganic perovskite materials, the relevant performance of the functional current collector changes from high to low, that is, using non-chiral two-dimensional hybrid organic-inorganic perovskite materials is more conducive to improving the various performances of the functional current collector and optimizing the comprehensive performance of the functional current collector.

[0054] By comparing Example 1 and Example 5, Example 2 and Example 6, Example 3 and Example 7, and Example 4 and Example 8, it can be found that when two-dimensional hybrid organic-inorganic perovskite materials of different chiral types are used, the thickness of the coating formed is limited to a certain range, which is more conducive to making the performance of the coating better, and making the various performances of the final functional current collector more excellent.

[0055] Comparing Example 3 and Example 9, and Example 2 and Example 10, the hybrid organic-inorganic perovskite coating is not in the range of 130~170nm, resulting in a decrease in various performances of the hybrid organic-inorganic perovskite coating. This is because the hybrid organic-inorganic perovskite coating is part of the functional current collector, and together with other coatings and the base film, it constitutes an overall functional current collector. A hybrid organic-inorganic perovskite coating that is too thin or too thick will affect its performance on other coatings or its own performance, thereby affecting the overall performance of the final functional current collector.

[0056] Comparing Example 1 with Examples 11 and 12, when the thickness of the oxide coating or the metal layer is not within a specific numerical range (the thickness of the oxide coating of Example 11 is not within the range of 50-200 nm, and the thickness of the metal layer of Example 12 is not within the range of 0.8-1.2 μm), the relevant performance of the functional current collector will also be affected. This shows that when all layers in the functional current collector are within a certain range, it is more conducive to the overall performance of the functional current collector, that is, it is more conducive to the comprehensive performance of the functional current collector.

[0057] Comparing Example 1 and Example 13, when the oxide coating and the metal layer are replaced with other materials, the functional current collector finally prepared also has good performance in all aspects.

[0058] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A functional current collector, characterized in that: It includes a base film, a hybrid organic-inorganic perovskite coating, and a metal layer in sequence; The material of the hybrid organic-inorganic perovskite coating includes a two-dimensional hybrid organic-inorganic perovskite material; the two-dimensional hybrid organic-inorganic perovskite material includes at least one of an achiral two-dimensional hybrid organic-inorganic perovskite material, a mixed achiral two-dimensional hybrid organic-inorganic perovskite material, a semi-chiral two-dimensional hybrid organic-inorganic perovskite material, and a fully chiral two-dimensional hybrid organic-inorganic perovskite material.

2. The functional fluid collector according to claim 1, characterized in that: The thickness of the hybrid organic-inorganic perovskite coating is 130-170 nm.

3. The functional fluid collector according to claim 2, characterized in that: When the material of the hybrid organic-inorganic perovskite coating includes the non-chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 145-155 nm; When the material of the hybrid organic-inorganic perovskite coating includes the mixed non-chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 155-165 nm; When the material of the hybrid organic-inorganic perovskite coating includes the semi-chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 135-145 nm; When the material of the hybrid organic-inorganic perovskite coating includes the chiral two-dimensional hybrid organic-inorganic perovskite material, the thickness of the hybrid organic-inorganic perovskite coating is 148-158 nm.

4. The functional fluid collector according to claim 1, characterized in that: The non-chiral two-dimensional hybrid organic-inorganic perovskite material includes [C4A]2PbI4; The mixed achiral two-dimensional hybrid organic-inorganic perovskite material includes [C4A]2[PEA]PbI4; The semi-chiral two-dimensional hybrid organic-inorganic perovskite material includes [SMePEA][C3A]PbI4; The chiral two-dimensional hybrid organic-inorganic perovskite material includes [SMePEA]2PbI4; Among them, in [C4A]2PbI4, [C4A]2[PEA]PbI4, [SMePEA][C3A]PbI4 and [SMePEA]2PbI4, C4A is C4NH3 + , PEA is , S indicates that the structure is left-handed, Me is methyl, SMePEA is , C3A is .

5. The functional fluid collector according to claim 1, characterized in that: When the material of the hybrid organic-inorganic perovskite coating includes at least one of the achiral two-dimensional hybrid organic-inorganic perovskite material and the mixed achiral two-dimensional hybrid organic-inorganic perovskite material.

6. The functional fluid collector according to claim 3, characterized in that: The thickness of the base film is 6-8 μm; the thickness of the metal layer is 0.8-1.2 μm.

7. The functional fluid collector according to any one of claims 1 to 6, characterized in that: The method comprises the base film, the hybrid organic-inorganic perovskite coating, the oxide coating and the metal layer in sequence.

8. The functional fluid collector according to claim 7, characterized in that: The thickness of the oxide coating is 0.5-20 nm.

9. The functional current collector according to claim 7, characterized in that: The material of the base film includes at least one of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide; The material of the oxide coating includes at least one of aluminum oxide and silicon oxide; The material in the metal layer includes at least one of aluminum, copper, manganese, lithium and zinc.

10. The method for preparing the functional fluid collector according to claim 7, characterized in that: The steps include: S1. preparing a hybrid organic-inorganic perovskite mixture, applying the mixture to the surface of the base film, and drying to form the hybrid organic-inorganic perovskite coating on the surface of the base film; S2. Continuing to deposit the oxide coating on the surface of the hybrid organic-inorganic perovskite coating; the deposition method includes at least one of magnetron sputtering and vacuum coating; S3. Continue to deposit the metal layer on the surface of the oxide coating; the deposition method includes at least one of magnetron sputtering and vacuum coating.

Citation Information

Patent Citations

  • Preparation method of organic and inorganic hybrid perovskite material and new application

    CN105895916A

  • Copper current collector with double-layer composite protection layer structure

    CN212725380U

  • Redox active mass for a chemical looping combustion process

    US20070049489A1

  • Protective Coatings for Metal Alloys and Methods Incorporating the Same

    US20120264031A1